Respuesta :
a₂ = 6 a₄ = 54
[tex] a_{n} = q^{n-1} * a_{1} [/tex]
[tex] \left \{ {{ a_{2} = q^{2-1} * a_{1} } \atop { a_{4} = q^{4-1}* a_{1} }} \right. \\ \\ \left \{ {{6 = q * a_{1} } \atop {54 = q^{3} * a_{1} }} \right. \\ \\ \left \{ {{ a_{1} = \frac{6}{q} } \atop {54 = q^{3} * \frac{6}{q} }} \right. \\ \\ \left \{ {{ a_{1} = \frac{6}{q} } \atop {54 = q^{2} * 6 }} \right. [/tex]
[tex] \left \{ {{ a_{1} = \frac{6}{q} } \atop { q^{2} =9}} \right. \\ \\ \left \{ {{ a_{1} = \frac{6}{q} } \atop {q= \sqrt{9} }} \right. [/tex]
q = 3 q = -3
a₁ = 6/3 = 2 a₁ = 6/-3 = -2
[tex] a_{n} = q^{n-1} * a_{1} [/tex]
[tex] \left \{ {{ a_{2} = q^{2-1} * a_{1} } \atop { a_{4} = q^{4-1}* a_{1} }} \right. \\ \\ \left \{ {{6 = q * a_{1} } \atop {54 = q^{3} * a_{1} }} \right. \\ \\ \left \{ {{ a_{1} = \frac{6}{q} } \atop {54 = q^{3} * \frac{6}{q} }} \right. \\ \\ \left \{ {{ a_{1} = \frac{6}{q} } \atop {54 = q^{2} * 6 }} \right. [/tex]
[tex] \left \{ {{ a_{1} = \frac{6}{q} } \atop { q^{2} =9}} \right. \\ \\ \left \{ {{ a_{1} = \frac{6}{q} } \atop {q= \sqrt{9} }} \right. [/tex]
q = 3 q = -3
a₁ = 6/3 = 2 a₁ = 6/-3 = -2